An Overview of Dye Wastewater and Its Treatment via Coagulation-Flocculation with Iron Chloride - Abbas, Mohanad Jawad; Al-Sahari, Mohammed; Radin Mohamed, Radin Maya Saphira; Saeed Al-Gheethi, Adel Ali (Penerbit UTHM, 2020)
The chapter discusses an overview of the removal of colour, COD, turbidity and TSS from dye wastewater using iron chloride as a coagulant in coagulation-flocculation process. This chapter explained dye wastewater definition and characteristics, dye wastewater treatment methods and factors that influence the coagulation-flocculation processes of dye wastewater treatment. The chapter also gives an explanation about various chemical coagulant used in dye wastewater treatment process and the efficiency of these coagulants.